Sponge-Associated Actinobacteria: Morphological Character and Antibacterial Activity against Pathogenic Bacteria - DITA, SASMIATI FARACH; BUDIARTI, SRI; LESTARI, YULIN (Jurnal Sumberdaya Hayati, 2017)
Sponge-associated actinobacteria may diverse and have potency to produce bioactive compounds. Diversity and antimicrobial activity of indigenous sponge-associated actinobacteria isolated from the marine ecosystem in Indonesia have not much been explored. This work aimed to assess morphological and antibacterial activity of sponge-associated actinobacteria. The morphological characteristics were examined based on their color of aerial and substrate mycelia, and pigmentation, while antibacterial activities were assayed using the antagonist technique. The selected actinobacterial isolate was identified using 16S rRNA gene. Various sponge-associated actinobacteria were successfully isolated from Hyrtios sp., Callyspongia sp., and Neofibularia sp. sponges. A total of 62 actinobacterial isolates were obtained, and each isolate showed a variety of morphological characters, which could be seen in aerial mass color, substrate mass color, and pigmentation. Actinobacterial isolates were tested against human pathogenic bacteria, i.e. Staphylococcus aureus and Methicillin-Resistant S. aureus, representing Gram-positive, and Escherichia coli EPEC K1-1 and Shigella dysenteriae, representing Gram-negative. Most of actinobacterial isolates had antimicrobial activities at least against one of pathogenic bacteria. High activity was shown by NOHa.2, isolated from Neofibularia, and HRHa.5 isolated from Hyrtios. The NOHa.2 showed the highest antimicrobial activity against S. dysenteriae, meanwhile, HRHa.5 showed antimicrobial activity against 3 of 4 tested bacterial pathogens. These data showed diversity of sponge-asccociated actinobacteria from marine ecosystem in Indonesia, and several of them have potency as source of antibacterial compounds